Effects of Sevoflurane Inhalation Anesthesia on the Intestinal Microbiome in Mice - Han, Ci; Zhang, Zhaodi; Guo, Nana; Li, Xueting; Yang, Mengyuan; Peng, Yahui; Ma, Xiaohui; Yu, Kaijiang; Wang, Changsong (Frontiers in Cellular and Infection Microbiology, 2021)
In recent years, more and more attention has been paid to intestinal microbiome. Almost all operations will go through the anesthesia process, but it is not clear whether the intervention of anesthesia alone will affect the change in the intestinal microbiome. The purpose of this study was to verify the effect of sevoflurane inhalation anesthesia on the intestinal microbiome. The animal in the experimental group was used to provide sevoflurane inhalation anesthesia for 4 hours. The control group was not intervened. The feces of the experimental group and the control group were collected on the 1st, 3rd, 7th and 14th days after anesthesia. Sevoflurane inhalation anesthesia will cause changes in the intestinal microbiome of mice. It appears on the 1st day after anesthesia and is most obvious on the 7th day. The specific manifestation is that the abundance of microbiome and the diversity of the microbiome is reduced. At the same time, Untargeted metabonomics showed that compared with the control group, the experimental group had more increased metabolites related to the different microbiome, among which 5-methylthioadenosine was related to the central nervous system. Subsequently, the intestinal microbiome diversity of mice showed a trend of recovery on the 14th day. At the genus level, the fecal samples obtained on the 14th day after anesthesia exhibited significantly increased abundances of Bacteroides, Alloprevotella, and Akkermansia and significantly decreased abundances of Lactobacillus compared with the samples obtained on the 1st day after anesthesia. However, the abundance of differential bacteria did not recover with the changing trend of diversity. Therefore, we believe that sevoflurane inhalation anesthesia is associated with changes in the internal microbiome and metabolites, and this change may be completed through the brain-gut axis, while sevoflurane inhalation anesthesia may change the intestinal microbiome for as long as 14 days or longer.